2020
DOI: 10.3892/ol.2020.11673
|View full text |Cite
|
Sign up to set email alerts
|

Fat mass and obesity-associated protein promotes the tumorigenesis and development of liver cancer

Abstract: Liver cancer is the fourth leading cause of cancer-associated mortality worldwide. Statistics indicate that the incidence of liver cancer has been increasing and that its prognosis remains poor. Fat mass and obesity-associated protein (FTO) is a demethylase that is involved in N6-methyladenosine (m6a) RNA modification; however, to the best of our knowledge, its role in tumorigenesis and development of liver cancer remains unknown. In the present study, cell proliferation, colony formation, apoptosis, Transwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It suggests that it may promote the proliferation and migration of hepatoma cells. In addition, upregulation of FTO expression in patients with liver cancer is associated with high Edmondson grade, which is an independent prognostic factor for liver cancer [ 87 ]. The study by Zhao et al showed that patients with decreased FTO expression had shorter overall survival and tumor-free survival compared with patients with normal FTO expression [ 88 ].…”
Section: Fto In Liver Cancermentioning
confidence: 99%
“…It suggests that it may promote the proliferation and migration of hepatoma cells. In addition, upregulation of FTO expression in patients with liver cancer is associated with high Edmondson grade, which is an independent prognostic factor for liver cancer [ 87 ]. The study by Zhao et al showed that patients with decreased FTO expression had shorter overall survival and tumor-free survival compared with patients with normal FTO expression [ 88 ].…”
Section: Fto In Liver Cancermentioning
confidence: 99%
“…Subsequently, tissue microarray slices were incubated for 16 h at 4°C with the primary antibody against DDX60L (dilution, 1:400; catalog number bs-14236R; Beijing Biosynthesis Biotechnology Co., Ltd.), followed by incubation with EnVision+ System-HRP (catalog number K4001, Dako). Finally, the staining was visualized with the DAB Substrate kit (catalog number DA1010-2, Solarbio) and counterstained with hematoxylin (22).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…The staining intensity was assessed using a fourgrade grading system: 3 (strong), 2 (moderate), 1 (weak), and 0 (negative). The percentage of DDX60L-positive cells was scored as follows: 0 (less than 5%), 1 (6-25%), 2 (26-50%), 3 (51-75%), and 4 (>75%) (22). The staining intensity scores and the percentage of positive cells were multiplied to obtain the final immunohistochemical staining score of DDX60L.…”
Section: Scoring Of Immunohistochemical Stainingmentioning
confidence: 99%
“…Several studies hold conflicting opinions against above results, suggesting that FTO was overexpressed in HCC and could promote proliferation and invasion. 47 , 48 According to a long-term mice experiment, FTO is essential for the control of energy balance and glucose metabolism. Importantly, during the initiation phase of tumor development, FTO is upregulated on acute liver damage but plays protective roles in HCC development.…”
Section: Role Of the Fto Gene In Digestive System Cancersmentioning
confidence: 99%